DEFECT ASSESSMENT IN CLADDED SEAMLESS PIPE UNDER TENSILE AND PRESSURE LOADING VIA FINITE ELEMENT METHOD - Basilio Pires Nonato, Raphael; Signorelli, Eduardo de Assunção (Revista Ciências Exatas, 2017)
Pipes are present in all sectors of society, including primary, genetic, extractive, manufacturing, construction, and service industries. Because of this massive presence worldwide, their importance is remarkable. In the oil and gas industry, one of their applications requires the cladding process, such that it is obligatory to inspect them in order to check if they are useful for performing their design functions. When defects are produced due to this process, it is advisable to measure and evaluate if they can be put into service or not. The general objective of this paper is to check the mechanical response of a cladded seamless pipe under tensile and pressure loading in the presence of defects due to the process of welding deposition. This research has practical character with quantitative approach (using Finite Element Method), making use of literature review, resulting in presenting von Mises stresses under the abovementioned conditions.